การศึกษาความสัมพันธ์ระหว่างภาวะอัลบูมินในเลือดต่ำกับการเกิดภาวะ เม็ดเลือดขาว ชนิดนิวโทรฟิลต่ำจากการรักษาด้วยยาเคมีบำบัดครั้งแรกในผู้ป่วยมะเร็งเต้านม - หทัยวรรณ รัตนบรรเจิดกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Background: Neutropenia following chemotherapy administration may frequently lead to a life-threatening infection. Unanticipated episodes of neutropenia may occur following the first cycle chemotherapy. Hypoalbuminemia is related with malnutrition and may be associated with severe neutropenia. Objective: Aim of this study was to evaluate the association of hypoalbuminemia and occurrence of chemotherapy induced severe neutropenia Method: We prospectively collected data of breast cancer patients who received treatment doxorubicin and cyclophosphamide (AC) regimen for any stage at the Oncology Unit. Correlations between patient’s characteristics and the occurrences of severe neutropenia, febrile neutropenia (FN) were analyzed. Result: Seventy-five breast cancer patients were included in this study. After the first cycle AC, 24% and 60% of patients developed grade 3 and 4 neutropenia respectively and 13% of patients developed FN. None of patients had hypoalbuminemia. Analyses for other predictive factors showed no statistical significant correlation between grade 4 neutropenia and clinical factors. Only low normal baseline absolute neutrophil count was significantly correlated to febrile neutropenia. Conclusion: We found no correlation between hypoalbuminemia and severe neutropenia. Simple clinical factors cannot reliably predict the first cycle FN in breast cancer patients receiving AC chemotherapy. For development of future predictive model, the complex relation within data sets should be taken into account such as novel biomarkers or genetic profiles.